Measuring Software Functionality Using Function Point Method Based On Design Documentation - Irawati, Anie Rose; Mustofa, Khabib (2012)

(untitled)
Estimated value of software as agreed by the end user and the developer team should be expressed in a certain magnitude, one of which is the measure of functionality. Function Point (FP) Method is one of the methods used to obtain the size of the functionality and can be used to estimate cost, duration, and amount of resources required by a software project. However, Function Point measurement is not simple and requires expertise in software analysis. Furthermore, the results of the calculation are considered valid if it is verified by someone with International Function Point User Group (IFPUG) certification. This research aims at designing and implementing a system that makes users convenient in analyzing software functionality size based on FP method referring to IFPUG CPM 4.3.1 standards. The system helps users to perform FP analysis in a faster and easier way without sacrificing accuracy.